PERAN BADAN PERMUSYAWARATAN DESA (BPD) DALAM PENYELENGGARAAN PEMERINTAHAN DESA DI DESA KEMIREN KECAMATAN GLAGAH KABUPATEN BANYUWANGI - Nur Rohimah, Wahyu; Wilujeng, Sri; Vitasari, Leni (JURNAL KATARSIS, 2025)
The main issue in this research is the suboptimal role of the Village Consultative Body (BPD) in the administration of village governance in Kemiren Village.BPD members still do not fully understand their duties and functions, resulting in ineffective oversight and the channeling of community aspirations.This research aims to analyze the role of the BPD in village governance and identify the factors that influence its performance.The focus of this research is to provide a clear picture of the challenges faced by the BPD in carrying out its functions.The research methodology used is a qualitative descriptive approach.Data were obtained through observation, interviews, and documentation to provide an in-depth understanding of the situation in the field.The data analysis process is carried out through reduction, presentation, and conclusion drawing.This research is located in Kemiren Village, Glagah District, Banyuwangi Regency.The purposive sampling technique was used to determine informants relevant to this research.The research results indicate that the BPD has not yet functioned optimally in accommodating and channeling the aspirations of the community.Many aspirations have not yet been realized, and communication between the BPD and the community is still lacking.The supervisory function carried out by the BPD is also not yet optimal, as most of it is still performed by the BPD chairman himself.This indicates the need for capacity building among BPD members so that they can perform their duties better.The conclusion of this study emphasizes the importance of better training and understanding for BPD members.The village government needs to provide support in the form of capacity development so that the BPD can function effectively.